2017
DOI: 10.1016/j.neuropharm.2017.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Targeting glutamatergic and cellular prion protein mechanisms of amyloid β-mediated persistent synaptic plasticity disruption: Longitudinal studies

Abstract: Alzheimer's disease amyloid-β (Aβ) oligomers are synaptotoxic, inappropriately increasing extracellular glutamate concentration and glutamate receptor activation to thereby rapidly disrupt synaptic plasticity. Thus, acutely promoting brain glutamate homeostasis with a blood-based scavenging system, glutamate-oxaloacetate transaminase (GOT), and blocking metabotropic glutamate 5 (mGlu5) receptor or its co-receptor cellular prion protein (PrP), prevent the acute inhibition of long-term potentiation (LTP) by exog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 87 publications
3
24
0
Order By: Relevance
“…However, no dose responsiveness, pharmacokinetic or mechanistic information was available . Administration of other anti‐PrP C antibodies into the CNS or as single bolus injections has demonstrated benefit for long term potentiation deficits caused by either Aßo injection or AD‐related transgenes . However, these studies have not defined the utility or pharmacokinetics of human anti‐PrP C antibodies in an administration paradigm that is amenable to translation for clinical dosing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no dose responsiveness, pharmacokinetic or mechanistic information was available . Administration of other anti‐PrP C antibodies into the CNS or as single bolus injections has demonstrated benefit for long term potentiation deficits caused by either Aßo injection or AD‐related transgenes . However, these studies have not defined the utility or pharmacokinetics of human anti‐PrP C antibodies in an administration paradigm that is amenable to translation for clinical dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting PrP C , either by genetic deletion of Prnp or binding by anti‐PrP C monoclonal antibodies, has shown promise preclinically . However, antibody studies have been limited to acute electrophysiological outcomes, to intracerebral doses or to large acute doses systemically.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing the binding of infectious prions to cell membrane-anchored PrP is currently under investigation as a means to treat transmissible spongiform encephalopathies (Klyubin et al, 2014b). Intriguingly, the binding of A␤ or ␣-synuclein oligomers to cellular prion protein (PrP C ) disrupts synaptic plasticity and impairs learning (Barry et al, 2011;Freir et al, 2011;Hu et al, 2014;Klyubin et al, 2014b;Ferreira et al, 2017;Zhang et al, 2017) and it has been suggested that PrP C may act as a molecular sensor for a broad range of oligomeric protein ligands (Resenberger et al, 2011;Béland and Roucou, 2012). Intriguingly, like A␤ oligomers (Chen et al, 2010;Freir et al, 2011;Fluharty et al, 2013), full-length recombinant tau has been reported to bind to recombinant PrP in vitro (Wang et al, 2008) raising the prospect that at least some of tau's deleterious synaptic effects are mediated via cellular PrP C .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, NMDAR is also overactivated by infectious and toxic PrPD species binding to membrane PrPC, likely through the same mechanistic pathway as the oligomers of amyloid beta and alpha-synuclein, which subsequently activates the p38 Mitogen Activated Protein Kinase signaling pathway and induces neurotoxicity [23]. The activation of these downstream signaling pathways significantly disrupts both the propagation of action potentials and synaptic functions leading to impairment of LTP and LTD [15,23,45,47,48]. Together, the evidence suggests that, indirectly, PrPC normally acts as an upstream modulator of a wide variety of intracellular signaling pathways that are essential for neuronal activity.…”
Section: Prpc Regulates Major Intracellular Signaling Pathwaysmentioning
confidence: 99%